Quality of care and patient satisfaction amongst Caucasian and non-Caucasian patients: A mixed-method study in Australia. Issue 3 (7th March 2016) - Alizadeh, Somayeh; Chavan, Meena; Hamin, Hamin
Abstract : Purpose: – The purpose of this paper is to explore the key aspects of service quality within the outpatient context. The secondary aim is to compare views on quality of health service by Caucasian and non-Caucasian patients in Australia. Design/methodology/approach: – A mixed-method approach was adopted for this study. Qualitative data were collected from 40 patients to develop a scale for measuring health service quality. Quantitative data were collected using self-administered questionnaires available in English, Arabic, Persian, Chinese and Vietnamese. A total of 447 patients in six outpatient clinics completed the survey and data were analyzed using the structural equation modeling technique. Findings: – The qualitative findings determined eight dimensions of quality for outpatient care as follows: doctor professionalism; doctor empathy; doctor expertise; treatment outcome; staff concern; timeliness; tangibles; and operation. The quantitative findings indicated that factors related to technical aspect of care, including doctor expertise and treatment outcome were assumed the strongest predictors of overall health care quality in both Caucasian and non-Caucasian groups. Furthermore, no significant discrepancy was found between these two groups' ratings of overall service quality and satisfaction with care. Originality/value: – The study captured ethnically diverse patients' perspectives on health service quality and highlighted the significance of technical quality, which is generally neglected in service quality measures.